2020
DOI: 10.1371/journal.pone.0234113
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of perioperative outcomes in elderly (age ≧ 75 years) vs. younger men undergoing robot-assisted radical prostatectomy

Abstract: Objectives To investigate perioperative, oncologic, and functional outcomes of robot-assisted radical prostatectomy (RARP) in men of age � 75 years in comparison with younger men. Methods From November 2011 to December 2018, six hundred and thirty patients with prostate cancer underwent robot-assisted radical prostatectomy (RARP). A total of 614 patients were analyzed after excluding 16 patients who were treated with hormone therapy prior to RARP. Patients were divided into 2 groups based on their age (age � 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 26 publications
2
25
0
Order By: Relevance
“…We hypothesized that surgeon experience may be related to AUL and included surgeon experience as a factor, but we did not identify any association with the surgeon volume and AUL in our cohort. This may partly be due to the unique mentoring system we implemented, in which RARP was divided into sections, each with a designated time limit and blood loss criteria, and an experienced surgeon replaced an inexperienced surgeon for the remainder of the section upon exceeding the designated time or blood loss [ 10 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that surgeon experience may be related to AUL and included surgeon experience as a factor, but we did not identify any association with the surgeon volume and AUL in our cohort. This may partly be due to the unique mentoring system we implemented, in which RARP was divided into sections, each with a designated time limit and blood loss criteria, and an experienced surgeon replaced an inexperienced surgeon for the remainder of the section upon exceeding the designated time or blood loss [ 10 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The da Vinci surgical robot system (da Vinci-S or Xi®: Intuitive Surgical Incorporation, Sunnyvale, CA) was used in performing RARP. As described in our previous studies, RARP was performed using the transperitoneal, 6 port technique [ 10 , 11 ]. Sixteen patients were treated with androgen deprivation therapy prior to RARP and were excluded from this study.…”
Section: Methodsmentioning
confidence: 99%
“…However, there is yet no consensus on how these physiological changes are clinically reflected on perioperative adverse events. These effects are evaluated according to the Clavien–Dindo classification system in studies and are classified as class 4 and 5 complications 2,5,11,17 . In their recent review article, Mandel et al concluded that elderly patients (75 years or older) with higher ASA scores had an increased risk of experiencing perioperative adverse events compared with younger men 18 .…”
Section: Discussionmentioning
confidence: 99%